A novel technique to characterize procoagulant platelet formation and evaluate platelet procoagulant tendency in cats by flow cytometry - Shaverdian, Meg; Nguyen, Nghi; Li, Ronald H. L. (Frontiers in Veterinary Science, 2024)
IntroductionCardiogenic arterial thromboembolism (CATE) is a life-threatening complication of hypertrophic cardiomyopathy (HCM) with a high mortality rate. As the primary responders in hemostasis, platelets play a crucial role in the progression of CATE. Procoagulant platelets are a subpopulation of activated platelets that facilitate thrombin generation to strengthen thrombus structure. Since their discovery, procoagulant platelets have gained a considerable amount of attention due to their potential role in thromboembolic complications. Uncovering the key phenotypic markers and agonists underlying the procoagulant response in feline platelets may provide diagnostic and therapeutic insights in the treatment of CATE. However, species differences in platelet physiology and the sensitive nature of feline platelets pose some significant challenges in studying procoagulant platelets in cats.ObjectivesTo first devise a flow cytometric method to sequentially assess procoagulant platelet markers and to identify agonists that could induce procoagulant platelet phenotypes. Furthermore, a novel scoring system was established to evaluate the procoagulant tendency of platelets in cats.MethodsPlatelets were isolated from eight healthy cats and activated by thrombin in the presence or absence of collagen (COL) and convulxin (CVX). The following markers were measured sequentially by flow cytometry: (1) loss of mitochondrial membrane potential (ΔΨm), (2) phosphatidylserine (PS) externalization, and (3) P-selectin upregulation.ResultsThrombin in the presence of CVX significantly reduced ΔΨm and induced P-selectin upregulation (p = 0.0078, p = 0.0128, respectively). In addition, thrombin-treated platelets in the presence of COL and CVX augmented PS externalization significantly (p = 0.043, p = 0.0172, respectively). Of the agonists tested, thrombin and CVX resulted in the highest procoagulant tendency score with 75% cats reaching a score ≥2/3. The number of cats with a procoagulant tendency score of 2 or 3 for thrombin and thrombin + COL was 4/8 (50%) and 5/8 (62.5%), respectively.DiscussionSequential analysis of procoagulant markers via flow cytometry may be an effective technique for studying procoagulant platelets in cats.